Lack of association of IL6R rs2228145 and IL6ST/gp130 rs2228044 gene polymorphisms with cardiovascular disease in patients with rheumatoid arthritis - López-Mejías, R.; García-Bermúdez, M.; González-Juanatey, C.; Castañeda, S.; Miranda-Filloy, J. A.; Gómez-Vaquero, C.; Fernández-Gutiérrez, B.; Balsa, A.; Pascual-Salcedo, D.; Blanco, R.; González-Álvaro, I.; Llorca, J.; et al. (Tissue antigens, 2011)
Interleukin‐6 (IL‐6) is a key mediator of inflammation in rheumatoid arthritis (RA) and its actions may be controlled by the IL‐6 receptor (IL‐6R). IL‐6 transducer (IL‐6ST/ gp130) is the signal transducing subunit of the IL‐6R. We assessed the influence of the IL6R and the IL6ST/gp130 genes in the risk of cardiovascular (CV) disease in RA. For this purpose, 1250 Spanish patients with RA were genotyped for the IL6R rs2228145 and IL6ST/gp130 rs2228044 functional gene polymorphisms. Patients were stratified according to the presence or absence of CV events. Also, a subgroup of patients without CV events was assessed for the presence of subclinical atherosclerosis using two surrogate markers of atherosclerosis (flow‐mediated endothelium‐dependent vasodilatation and carotid intima‐media thickness). No significant differences in the genotype and allele frequencies for both gene polymorphisms between patients with and without CV events were observed. It was also the case when values of surrogate markers of atherosclerosis were compared according to IL6R and IL6ST genotype frequencies. In conclusion, our results do not confirm an association of IL6R rs2228145 and IL6ST/gp130 rs2228044 polymorphisms with CV disease in RA.